THE PHENOMENON OF GREEN TRADE PROTECTIONISM: ANALYSIS OF THE EU PALM OIL IMPORT BAN IN THE ASEAN REGION - Maretha Syawallin Umarach (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: The policy issued by the European Union is the Renewable Energy Directive (RED) that turn creates barriers to palm oil exports from other countries to the European Union. The policy to ban palm oil under the pretext of protecting the environment is considered to be a new obstacle to trade. One of the rejection responses came from the ASEAN region. However, even though it has received a lot of protests and rejections, until 2020 the European Union has not changed its policy regarding the ban on the use of palm oil for biodiesel in the European region.Methods: This article focuses on the reasons for the European Union implementing protectionism policies towards the Palm Oil sector in the ASEAN region. The explanation regarding this focus is explained using the Neo Mercantilism approach.Results: The policy to ban palm oil imports can be analyzed to respond to the EU's ambition and concern that the climate emergency will jeopardize the trade process in the future. The European Union research group considers that oil palm plants have a high contribution to the problem of deforestation and forest and peatland diversion in the world, especially ASEAN. Howeever, it can also be seen that there are ambitions to protect the domestic production of biofuels from the EU sunflower and radishes from global competition. The above concerns and motivations then prompted the European Union to formulate protectionism for regional economic stability.Conclusion and suggestion: ASEAN, especially Indonesia and Malaysia, have become quite vocal actors in responding to this policy. Indonesia and Malaysia are the biggest contributors of palm oil exports to Europe. As well as causing an oversupply of global palm oil supplies, this policy is considered to discriminate against and violate free-trade norms.